Emu-miR-10a-5p in Echinococcus multilocularis-derived-extracellular vesicles alleviates airway inflammation in mice with allergic asthma by inhibiting macrophage M2a polarization through LIF-mediated JAK1–STAT3 signaling - Xin, Yunzhuo; Wen, Rou; Song, Dong; Xiao, Jing; Gao, Xiaoping; Yin, Mei; Bai, Yanli; Wang, Jie; Zhou, Xiangyu; Zhao, Jiaqing (Frontiers in Immunology, 2025)
IntroductionParasites and parasite-derived extracellular vesicles (EVs) and microRNAs (miRNAs) can protect against inflammatory diseases, such as asthma. M2a macrophages facilitate the development of allergic asthma. miR-10a-5p is closely associated with asthma, and emu-miR-10a-5p (encapsulated in Echinococcus multilocularis EVs), shares seed-site sequences with mature human and mouse miRNAs.MethodsWe purified EVs by centrifugation, and characterized the EVs via nanoparticle tracking analysis (NTA) and transmission electron microscopy (TEM). We used MH-S cells to construct the M2a polarization model. The gene expression changes in MH-S cells after transfect with emu-miR-10a-5p mimics was analyzed through transcriptome sequencing. We established a mouse model of ovalbumin (OVA)-induced allergic asthma. Hematoxylin and eosin (H&E), Masson’s trichrome, and periodic acid–Schiff (PAS) staining were used to detect airway inflammation in the lung tissues. RT-qPCR, flow cytometry and Western Blot assays were performed to validate the expression of related genes and proteins.ResultsHere, we observed that E. multilocularis-derived EVs and their encapsulated emu-miR-10a-5p transcripts inhibited macrophage M2a polarization. We also found that emu-miR-10a-5p targeted leukemia inhibitory factor (LIF) mRNA and inhibited the downstream Janus kinase 1 (JAK1)–signal transducer and activator of transcription 3 (STAT3)-signaling pathway. We established a mouse model of ovalbumin (OVA)-induced allergic asthma and found that emu-miR-10a-5p alleviated pulmonary inflammation in mice with allergic asthma while inhibiting the accumulation of pulmonary M2a macrophages. emu-miR-10a-5p intervention inhibited LIF and JAK1–STAT3 signaling in the lungs of mice with allergic asthma.DiscussionThese findings suggest that emu-miR-10a-5p encapsulated in E. multilocularis EVs might regulate M2a macrophage polarization via the JAK1–STAT3 pathway by targeting and binding LIF in a cross-species manner, thereby alleviating airway inflammation in mice with allergic asthma. These findings enhance the current understanding of the mechanisms underlying immune regulation during infection and the maintenance of immune stability.